2023
DOI: 10.1101/2023.07.25.550556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analysis of DNA replication origins and ORC/MCM binding sites in human cells reveals a lack of overlap

Abstract: DNA replication initiates from ~50,000 origins on human chromosomes in each cell-cycle and the origins are hypothesized to be specified by binding of factors like the Origin Recognition Complex (ORC) or CTCF or other features like G-quadruplexes. We have performed an integrative analysis of 113 genome-wide human origin profiles (from five different techniques) and 5 ORC-binding site datasets to critically evaluate whether the most reproducible origins are specified by these features. Out of ~7.5 million 300 bp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…The Dutta and Zang labs have recently suggested that the origins are specified by diverse stochastic events that are dependent on the epigenetic accessibility around promoters. However, intriguingly, the ORC-binding sites or the MCM complex did not overlap with the origins [ 49 ]. A series of genome-wide studies with various ORC antibodies, specifically at distinct time points within G1, would be important to pinpoint ORC dynamics in human cells.…”
Section: Chromatin Signature At the Originsmentioning
confidence: 99%
“…The Dutta and Zang labs have recently suggested that the origins are specified by diverse stochastic events that are dependent on the epigenetic accessibility around promoters. However, intriguingly, the ORC-binding sites or the MCM complex did not overlap with the origins [ 49 ]. A series of genome-wide studies with various ORC antibodies, specifically at distinct time points within G1, would be important to pinpoint ORC dynamics in human cells.…”
Section: Chromatin Signature At the Originsmentioning
confidence: 99%
“…In these inverted ORC-binding sites in proximity, a MCM double hexamer is recruited at or very near to the site where ORC is bound, and replication initiation takes place. This mechanism is unlikely to work in the case of humans where replication origins are devoid of conserved sequence motifs in proximity specific for ORC binding [59,60]. Without a second binding site in proximity, wherever ORC binds, it will only recruit a single MCM hexamer [61].…”
Section: Pre-rc Assembly In Yeast and In Humansmentioning
confidence: 99%
“…In the larger genomes of mammals, identification of origins has proved more challenging due to a lack of consistency between datasets that map DNA replication initiation, or localisation of ORC 1, 16 . In part, such inconsistency may be due to mammalian origins not being sequence-conserved genome features, but could also reflect greater use of stochastic, potentially ORC-independent initiation than is seen in yeast 1721 . Nonetheless, mammalian replication timing appears to be organised over several scales.…”
Section: Introductionmentioning
confidence: 99%